INDONESIA'S POLICY OF PALM OIL EXPORTS BANNED IN THE CURRENT WORLD ENERGY CRISIS - Alana Sabila; Hanindya Aditama (Ikatan Dosen Menulis, 2023)
This paper aims to determine the impact of tariff and non-tariff barriers, the ban on exports of palm oil commodities, and the energy crisis due to the Russia-Ukraine war on the Indonesian and world economies. The research was conducted because it wanted to know the impact of the policies carried out by the Indonesian government as the largest producer of palm oil in the world and whether it produced a spillover effect on the economy. The objective is to examine the policies set by the government, namely tariff or non-tariff barriers, and their impact on trade. The Indonesian government implemented a policy banning palm oil exports from reducing the sharply rising local palm oil prices and meeting domestic demand. The policy was implemented in March 2022 and required further research to analyze its impact. This study used the GTAP database analysis tool in 2011. This study includes shocks in tariff and non-tariff barriers on palm oil commodities. The shock that was included to represent the energy crisis was a ban on exports and imports to Russia and a ban on food exports in Ukraine. The study results using the GTAP analysis tool, namely the determination of the export ban on palm oil commodities, had a positive impact, namely reducing the price of domestic palm oil, but the negative impact was the level of output, and the number of workers fell. Increasing export tariffs is not effective and increases domestic palm oil prices. Government policies that are carried out must ensure that domestic palm oil has stocks that meet consumption at affordable prices. The government must implement policies that protect consumers and producers of palm oil. Policies that the government can carry out are mitigating safety nets and distributing aid directly to affected society.